Fauna and conservation in the context of formal education: a study of urban and rural students in the semi-arid region of Brazil - de Oliveira, José Valberto (J Ethnobiol Ethnomed, 2020)
BACKGROUND: In addition to playing a key role in the dynamics of ecosystems, animal diversity, especially that of wild vertebrates, is intimately linked with human evolutionary history, which has resulted in diverse interactions that must be emphasized in formal education processes. We analyzed several methods of approaches used for biological education in order to teach about wild vertebrates and their conservation in urban and rural schools in the semi-arid region of Brazil. METHODS: Data were obtained via questionnaires applied to 990 students, of which 528 were urban and 462 rural, distributed among the seven grades/years that comprise the last two cycles of basic education in Brazil. The richness and diversity of the animals cited by the students were calculated, being the diversity using an adaptation of the equation for the Shannon-Weaver Index (H′). Data were analyzed using non-parametric descriptive statistics. RESULTS: Mammals and birds had the greatest richness and diversity of animals cited as most-studied in science/biology classes, and also the most indicated as occurring in the studied region. Among mammals, large carnivores with a showy appearance and utilitarian value had the highest citation frequencies, while there was a tendency for limited recognition of faunistic diversity in the other groups mentioned. Almost 70% of the students stated that their schooling processes dealt with the conservation of wild animals; however, about 50% of the students in both urban and rural contexts did not express conceptual understanding about the conservation of nature. CONCLUSIONS: The recognition of animal diversity, especially vertebrates, beyond just mammals and birds, as well as conceptual clarity about the conservation of nature, are fundamental factors for the development of critical awareness of fauna and its conservation, and where the processes of schooling have a preponderant role. Finally, the study contributes to the legitimization of Ethnobiology as an interdisciplinary field of knowledge, especially in its interface with education, in addition to pointing out the importance of optimizing efforts in approaches to biodiversity conservation in formal educational processes.